Towards low-emission food systems in Côte d’Ivoire: A country profile - Pingault, N.; Martius, C. (CIFOR-ICRAF, 2026)
Food systems—spanning agriculture, land use and land-use change and forestry (LULUCF), energy, industry, and waste—account for about one third of global anthropogenic greenhouse gas emissions, yet they remain an often underreported component of the climate challenge. This country profile on Côte d’Ivoire is part of a series of national analyses that apply a food-system lens to emissions by comparing FAOSTAT estimates with official national data from the country’s Biennial Transparency Report and Nationally Determined Contribution. It provides an integrated overview of land use, forests and agriculture, food security and diets, and food system emissions in Côte d’Ivoire, a country where rapid population growth, cocoa-driven deforestation, and rising urban demand interact with significant mitigation opportunities. The profile identifies a set of no-regret priorities for mitigation action that can reduce emissions while supporting food security and sustainable development, including forest-positive cocoa systems, improved livestock productivity, conservation of wetlands and organic soils, climate-smart rice cultivation, low-emission aquaculture and fisheries, and modern waste management. By making food system emissions more visible and policy-relevant, this publication aims to support national and international stakeholders in identifying mitigation pathways that deliver climate, food security, and development benefits in Côte d’Ivoire.